1975
DOI: 10.1038/bjc.1975.94
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic fibroblasts sensitive to the growth inhibition by homologous cells but insensitive to inhibition by parent normal cells

Abstract: Summary-3H-thymidine labelling and autoradiography were used to compare density dependent inhibition of growth in the cultures of two transformed lines of hamster fibroblasts and in primary cultures of their parent normal cells. Similar manifestations of density dependent inhibition were found in the isolated cultures of normal and neoplastic cells: at saturation densities these cultures had low labelling indices; these indices considerably increased when the cells migrated into the wound from the dense sheet,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Figure 4 shows that in a checkerboard consisting of y-irradiated monolayers of BMS, Cl4, CZl, and C23 cells (rows) overlaid with no cells or lo4 BMS,C14,C21,or C23 cells (columns), all cell types could form colonies on all others, except for BMS, C14, and C23 cells on C23 monolayers. The reasons for such selective growth abilities are unknown, hut several similar instances have been reported from which no clear pattern has emerged (Stoker, 1964;Ponten and MacIntyre, 1968;Eagle et al, 1968;Weiss, 1970;Pletyushkina et al, 1975;Sakiyama et al, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 shows that in a checkerboard consisting of y-irradiated monolayers of BMS, Cl4, CZl, and C23 cells (rows) overlaid with no cells or lo4 BMS,C14,C21,or C23 cells (columns), all cell types could form colonies on all others, except for BMS, C14, and C23 cells on C23 monolayers. The reasons for such selective growth abilities are unknown, hut several similar instances have been reported from which no clear pattern has emerged (Stoker, 1964;Ponten and MacIntyre, 1968;Eagle et al, 1968;Weiss, 1970;Pletyushkina et al, 1975;Sakiyama et al, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that sensitivity to topoinhibition by homologous cells is not always completely lost after transformation (Westermark, 1973;Risser and Pollack, 1974;Pletyushkina et al, 1975) although the saturation density at which topoinhibition is observed may increase after transformation. I n particular, L-cells, the parent strain of LSF subline, were found to be sensitive to topoinhibition (Domnina et al, 1972).…”
Section: Alterations Of Growth Characteristics Induced By Serummentioning
confidence: 99%